Building Synthetic Sterols Computationally – Unlocking the Secrets of Evolution? - Róg, Tomasz; Pöyry, Sanja; Vattulainen, Ilpo (Frontiers in Bioengineering and Biotechnology, 2015)
Cholesterol is vital in regulating the physical properties of animal cell membranes. While it remains unclear what renders cholesterol so unique, it is known that other sterols are less capable in modulating membrane properties, and there are membrane proteins whose function is dependent on cholesterol. Practical applications of cholesterol include e.g. its use in liposomes in drug delivery and cosmetics, cholesterol-based detergents in membrane protein crystallography, and its fluorescent analogs in studies of cholesterol transport in cells and tissues. Clearly, in spite of their difficult synthesis, producing the synthetic analogs of cholesterol is of great commercial and scientific interest. In this article, we discuss how synthetic sterols nonexistent in nature can be used to elucidate the roles of cholesterol's structural elements. To this end, we discuss recent atomistic molecular dynamics simulation studies that have predicted new synthetic sterols with properties comparable to those of cholesterol. We also discuss more recent experimental studies that have vindicated these predictions. The paper highlights the strength of computational simulations in making predictions for synthetic biology, thereby guiding experiments.